2006
DOI: 10.1111/j.1365-2249.2006.03008.x
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor (TLR) 4 polymorphisms are associated with a chronic course of sarcoidosis

Abstract: SummaryThe aetiology of sarcoidosis, an inflammatory granulomatous multi-system disorder, is unclear. It is thought to be the product of an unknown exogenous antigenic stimulus and an endogenous genetic susceptibility. Toll-like receptors (TLR) are signal molecules essential for the cellular response to bacterial cell wall components. Lipopolysaccharide (LPS), for example, binds to TLR 4. Two different polymorphisms for the TLR4 gene (Asp299Gly and Thr399Ile) have been described recently. This leads to a chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 57 publications
7
50
1
2
Order By: Relevance
“…In prior studies, the course of sarcoidosis disease has been characterised as chronic if disease activity persisted beyond 2 years [11][12][13][14][15][16]. As such, the 2-year threshold was incorporated into our classification schema.…”
Section: Study Subjectsmentioning
confidence: 99%
“…In prior studies, the course of sarcoidosis disease has been characterised as chronic if disease activity persisted beyond 2 years [11][12][13][14][15][16]. As such, the 2-year threshold was incorporated into our classification schema.…”
Section: Study Subjectsmentioning
confidence: 99%
“…For sarcoidosis, polymorphisms in several genes (NRAMP, TLR4, HLA, Vitamin D receptor) involved in the immune response to exogenous pathogens have been investigated [1,[35][36][37], suggesting that exposure to environmental factors capable of eliciting these pathways may be important in development of sarcoidosis. Polymorphisms in the vitamin D receptor are intriguing, and have been used in conjunction with an internal phenotype (Vitamin D deficiency) to suggest the presence of a gene-environment interaction between diet and VDR for risk of pulmonary tuberculosis among Gujaratis [38].…”
Section: Modeling Interactionsmentioning
confidence: 99%
“…[62] Several studies in German and Dutch cohorts have investigated the potential association of polymorphisms in the TLR4, TLR2 and TLR9 genes with sarcoidosis but found no association with the risk of sarcoidosis. [63][64][65][66][67] One study in a German cohort suggested an association with chronic sarcoidosis. [63] In a Dutch cohort, SNPs rs1109695 and rs7658893 in the TLR-10 gene and rs57436004 and rs5743594 in the TLR-1 gene were associated with the risk of sarcoidosis.…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…[63][64][65][66][67] One study in a German cohort suggested an association with chronic sarcoidosis. [63] In a Dutch cohort, SNPs rs1109695 and rs7658893 in the TLR-10 gene and rs57436004 and rs5743594 in the TLR-1 gene were associated with the risk of sarcoidosis. [68] None of the 4 SNPs were significantly different between remitting and chronic disease but they did differ significantly between healthy controls and sarcoidosis patients with chronic/progressive disease.…”
Section: Toll-like Receptorsmentioning
confidence: 99%